Criminological characteristics of crimes in bankruptcy - Butyrskyi, Andrii (My University, 2021)
The article is devoted to investigating the problems of the causes of crimes in bankruptcy proceedings. The purpose of the article is to identify and analyze the causes of bankruptcy crimes achieved through the establishment of: types of bankruptcy crimes, subjects of bankruptcy crimes, motives for committing bankruptcy crimes, peculiarities of crimes at different stages of bankruptcy. The theoretical basis of the study was the scientific work of scientists and practitioners in the field of criminology, criminal law and economic law. The authors have developed their own concept, which is based on the so-called bankruptcy rhombus, which defines the composition and location of each of the participants in the bankruptcy case, is ideally suited to identify the subjects and object of the bankruptcy crime, because it allows you to see the degree of interest of participants in the case bankruptcy and their hierarchy. Now let’s look at the causes of the crime each participant individually, starting from the bottom of the rhombus – from the debtor. To achieve this goal and to solve it set of tasks during the study was used a set of various methods of cognition, among which can be distinguished: dialectical, systemic analysis, formal-logical, systemic-structural.
Keywords: bankruptcy; crime; criminology; debtor; creditor